Phase delay through slot-line beam switching microstrip patch array antenna design for sub-6 GHz 5G band applications - Das, Debprosad; Hossain, Md. Farhad; Hossain, Md. Azad; Rahman, Muhammad Asad; Hossain, Md. Motahar; Hossam-E-Haider, Md. (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Two, four, eight, and sixteen-element patch array antennas for beam switching are presented in this study. For a 1×2 array, an aperture-coupled feeding mechanism is used to feed patches while a slot line on the ground plane provides the phase delay between antenna elements. The 1×2 array is used to create the 2×2, 4×2, and 8×2 arrays, and an equal power divider provides the signal for each. For applications in the 5G sub-6 GHz frequency spectrum, the antennas are modeled. With -37.14 dB, -17.85 dB, -21.51 dB, and -26.03 dB return loss for two, four, eight, and sixteen-element array antennas respectively the simulation demonstrates that the antennas are properly matched at the resonant frequency. The antennas can switch its radiated beam to ±24o, ±24o, ±28o, and ±26o with gains of 8.97 dBi, 11.19 dBi, 13.23 dBi, and 16.24 dBi, respectively at the resonance frequency. The directivity of the proposed antenna is found to be 9.17 dBi, 11.20 dBi, 13.40 dBi, and 16.45 dBi respectively. The antennas are constructed with two 0.8 mm-thick Teflon substrate layers. The ground plane between the two substrate layers contains the aperture and the slot line that generates the phase delay.